Surveillance of omadacycline activity tested against clinical isolates from the USA: report from the SENTRY Antimicrobial Surveillance Program, 2019. (December 2021) - Pfaller, Michael A.; Huband, Michael D.; Shortridge, Dee; Flamm, Robert K.
Highlights: Omadacycline was active against Staphylococcus aureus isolates including 96.5% of MRSA. Omadacycline was active against 100.0% of Enterococcus faecalis isolates including VRE. Omadacycline was active against 99.8% of Streptococcus pneumoniae including penicillin-resistant strains. Omadacycline was active against 99.2% of all Streptococcus pyogenes isolates. Omadacycline inhibited 90.8% of all Acinetobacter baumannii isolates at ≤4 mg/L. ABSTRACT: Objectives: Omadacycline was tested against 7000 bacterial isolates collected prospectively from medical centres in the USA during 2019. Methods: Antimicrobial susceptibility testing was performed according to Clinical and Laboratory Standards Institute (CLSI) guidelines. Results: Omadacycline was active against: Staphylococcus aureus (MIC50/90, 0.12/0.25 mg/L; 98.3% susceptible), including methicillin-resistant S. aureus (MRSA); Enterococcus faecalis (MIC50/90, 0.06/0.25 mg/L; 100.0% susceptible), including vancomycin-resistant enterococci (VRE); Streptococcus pneumoniae (MIC50/90, 0.06/0.06 mg/L; 99.8% susceptible); viridans group streptococci, including Streptococcus anginosus group (MIC50/90, 0.03/0.06 mg/L; 100.0% susceptible); β-haemolytic streptococci, including Streptococcus pyogenes (MIC50/90, 0.06/0.12 mg/L; 99.2% susceptible); Enterobacterales (MIC50/90, 1/8 mg/L; 86.9% inhibited at ≤4 mg/L), including Escherichia coli (MIC50/90, 0.5/2 mg/L; 99.6% inhibited at ≤4 mg/L); Enterobacter cloacae (MIC50/90, 2/4 mg/L; 98.5% susceptible); Klebsiella pneumoniae (MIC50/90, 1/4 mg/L; 93.2% susceptible); Acinetobacter baumannii (MIC50/90, 0.5/4 mg/L; 90.8% inhibited at ≤4 mg/L); Haemophilus influenzae (MIC50/90, 0.5/1 mg/L; 100.0% susceptible); and Moraxella catarrhalis (MIC50/90, ≤0.12/0.25 mg/L). Conclusion: The 2019 in vitro activity of omadacycline against key Gram-positive and Gram-negative pathogens has not changed compared with the prior 3 years of surveillance in the SENTRY Antimicrobial Surveillance Program. Omadacycline merits further study in serious infections where resistant pathogens may be encountered.